Strategy for Raising Village Potential from Kuncen Hamlet to Bendungan Village, Kulon Progo Regency - Vicki Dwi Purnomo (Jurnal Ekonomi dan Bisnis Digital, 2023)
The background of this research is community participation in efforts to build village potential starting from the hamlet. The formulation of the problem in this research is 1) What is the planning strategy for building the potential of Bendungan village starting from the hamlet? 2) What are the obstacles faced in the planning strategy for building a village from Kuncen Hamlet, Wates District, Kulon Progo Regency? 3) What are the efforts to overcome obstacles in the village development planning strategy from hamlets? The primary data source is that there are 15 people who were interviewed. Data collection techniques in this study were library research, field studies (observations and interviews). Data analysis techniques in this study were collecting observation and interview data, interpreting observation and interview data, describing observation and interview data to answer the research problem formulation and drawing conclusions from observation and interview data to answer the research problem formulation. Based on the results of the research that 1) The village development planning strategy starting from Kuncen Hamlet, Wates District, Kulon Progo Regency in general can be implemented, 2) lack of awareness that village potential can be explored can be more beneficial for welfare.